"Us vs. them" or "us over them"? On the roles of similarity and status in M&As. Issue 1 (February 2016) - Yildiz, H. Emre
Highlights: This paper looks at neglected role of status differences in M&As. Similarity between merging organizations increase benevolence-based trust. Individuals develop competence-based trust toward high-status acquirer. Individuals exhibit favorable social preferences toward high-status acquire. Status and similarity create interesting tradeoffs for knowledge transfer in M&As. Abstract: This paper complements existing research on the role of cultural similarity in cross-border M&As by examining their effects in conjunction with relative status positions of merging entities. Two experimental studies with senior managers were conducted and reported. Whereas status breeds competence-based trust between acquirer and acquired unit, similarity is conducive to benevolence-based trust. Furthermore, higher status position of acquirer is shown to have significant effect on acquired unit members' social preferences toward the former (Study1). Lastly, similarity and status are found to have distinct and joint effects on knowledge transfer in M&As, which designate an interesting tradeoff between acquired unit members' perceptions of the credibility of the acquirer and the usefulness of the advice it provides (Study 2). Theoretical and practical implications of the findings are discussed.